Sodium ferric sulfate positive electrode material, preparation method thereof, positive electrode plate and sodium ion battery
By doping P elements and N elements on the carbon coating in the sodium ferrosulfate matrix, the problem of insufficient rate performance and cycle stability of sodium ferrosulfate positive electrode material is solved, and the performance improvement of the positive electrode material of sodium ion battery is achieved , has the characteristics of low cost and environmental protection.
Patent Information
- Application Number
- CN202411362751.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The current sodium ion battery positive electrode materials have poor rate performance and cycle stability, especially the reaction activity of sodium ferric sulfate materials is easily oxidized due to Fe2+, which limits its rate capability.
Doping P elements in the sodium ferric sulfate matrix and N elements on the carbon coating layer, a stable carbon film is formed by low temperature sintering, improving the structural stability of the material and ion/electron transfer channels.
The rate performance and cycle stability of the sodium ferric sulfate cathode material are significantly improved, production costs are reduced, and the preparation method is simple and easy to implement, and it is green and environmentally friendly.
Smart Images

Figure CN119252891A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium iron sulfate positive electrode material and a preparation method thereof, a positive electrode sheet, and a sodium ion battery. Background Art
[0002] As a promising technology for electric vehicles and stationary energy storage, sodium-ion batteries have advantages over lithium-ion batteries in terms of low-temperature performance, low cost, and abundant materials. Using the existing lithium-ion battery production infrastructure, sodium-ion batteries are also feasible for large-scale production.
[0003] Currently, there are layered oxides, polyanions and Prussian blue materials that are expected to be used in commercial applications. The structural phase change of layered oxides brings many unstable factors to the deintercalation of sodium ions, and the introduction of expensive Ni and Cu elements to improve performance is costly, which is not conducive to large-scale application in the future market. Prussian blue materials have a large number of Fe(CN)6 defects and crystal water in their structures, which lead to structural failure and gas production during the deintercalation of sodium ions, making commercial applications difficult. Polyanion compounds have a rigid open framework and can stably store sodium ions. In terms of resource costs, the abundance of Fe in the earth's crust is 5.00%, much higher than Mn, V, and Co. Iron-based polyanion compounds have cost-effectiveness advantages and are environmentally friendly.
[0004] Among various iron-based polyanion compounds, sodium iron sulfate cathode has the highest redox potential, about 3.8V, which is much higher than sodium iron pyrophosphate (3.10V) and sodium iron phosphate (2.90V). Due to similar reversible capacity, wide source of raw materials, and simple process preparation, the energy density, raw material cost and production cost of sodium iron sulfate material are far superior to other polyanion compounds. 2+ It is easy to be oxidized, which affects the reaction activity of the material, resulting in a decrease in rate performance and cycle stability. At the same time, the material itself has poor electronic conductivity, which may make it difficult for sodium ions to be deintercalated, thus limiting its rate capability. Currently, carbon coating has been widely used to improve the electrochemical properties of sodium iron sulfate materials, but the rate performance and cycle performance of conventional carbon-coated sodium iron sulfate positive electrode materials are still poor.
[0005] Therefore, how to improve the rate performance and cycle stability of sodium iron sulfate positive electrode materials is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a sodium ferric sulfate positive electrode material and a preparation method thereof, a positive electrode plate, and a sodium ion battery. The present invention improves the rate performance and cycle stability of the sodium ferric sulfate positive electrode material by doping the P element in the sodium ferric sulfate matrix and the N element on the carbon coating layer.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a sodium ferric sulfate positive electrode material, which includes a sodium ferric sulfate matrix, a surface of which is coated with a carbon coating layer, wherein the sodium ferric sulfate matrix is doped with the element P, and the carbon coating layer is doped with the element N.
[0009] The present invention improves the rate performance and cycle stability of the sodium ferric sulfate positive electrode material by doping the P element into the sodium ferric sulfate matrix and doping the N element onto the carbon coating layer.
[0010] Furthermore, the chemical formula of the sodium ferric sulfate matrix is Na 6-2x Fe x (SO4)3, wherein x = 1.5 to 2.0;
[0011] And / or, the median particle size Dv50 of the sodium iron sulfate positive electrode material is 2 to 6 μm;
[0012] And / or, the carbon coating layer has a thickness of 1 to 10 nm.
[0013] In a second aspect, the present invention provides a method for preparing the sodium iron sulfate positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0014] S1, mixing an iron source, a sodium source and a sulfur source to obtain a sodium iron sulfate precursor A;
[0015] S2, uniformly dispersing the sodium iron sulfate precursor A, the carbon source, and the amphiphilic molecule in an aqueous organic solvent for reaction, and then removing the organic solvent by evaporation to obtain a solid mixture B, wherein the polar hydrophilic end of the amphiphilic molecule includes a P-containing hydrophilic end and an N-containing hydrophilic end, and the non-polar hydrophobic end of the amphiphilic molecule includes a long hydrocarbon chain;
[0016] S3, sintering the solid mixture B at a low temperature under a protective gas atmosphere, and post-treating the sintered material to obtain the sodium iron sulfate positive electrode material.
[0017] Further, the iron source includes at least one of FeSO4, ferrous nitrate, ferrous oxalate, and ferrous chloride; the sodium source includes at least one of sodium sulfate, sodium carbonate, sodium bicarbonate, sodium fluoride, sodium dihydrogen phosphate, and an organic acid salt of sodium; the sulfur source includes at least one of FeSO4, sodium sulfate, ammonium sulfate, and sodium bisulfate;
[0018] And / or, in step S1, the molar ratio of the iron element in the iron source, the sodium element in the sodium source and the sulfur element in the sulfur source is consistent with the molar ratio of the iron element, the sodium element and the sulfur element in the sodium ferric sulfate matrix;
[0019] And / or, in step S1, the mixing includes ball milling mixing, the ball-to-material ratio of the ball milling mixing is (15-20):1, the rotation speed of the ball milling mixing is 200-500 r / min, and the ball milling mixing time is 4-6 h.
[0020] Further, in step S2, the carbon source includes at least one of acetylene black, biomass nanocarbon, glucose, sucrose, caramel, starch, CNTs, carbon quantum dots, and dextrin; the amphiphilic molecules include phosphate amphiphilic molecules containing nitrogen elements, or the amphiphilic molecules include P-containing amphiphilic molecule organic matter and N-containing amphiphilic molecule organic matter, wherein the phosphate amphiphilic molecules containing nitrogen elements include at least one of phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, aminopolyethylene glycol phospholipids, and sphingomyelin, the P-containing amphiphilic molecule organic matter includes at least one of phospholipid compounds that do not contain N, phosphatidic acid, and cardiolipin, and the N-containing amphiphilic molecule organic matter includes at least one of polyoxyethylene castor oil and polyacrylamide.
[0021] Furthermore, in step S2, the mass ratio of the sodium iron sulfate precursor A, the carbon source and the amphiphilic molecule is (95-98):(1-2):(1-3).
[0022] Furthermore, in step S2, the dispersion speed is 3000-5000 r / min, and the dispersion time is 2-4 h;
[0023] And / or, in step S2, the reaction temperature is 60-80°C, and the reaction time is 5-6h;
[0024] And / or, in step S2, the aqueous organic solvent includes at least one of ethanol, propanol, tetrahydrofuran, dipropylene glycol butyl ether, and propylene glycol methyl ether.
[0025] Furthermore, in step S3, the protective gas includes at least one of nitrogen, argon, hydrogen, and ammonia; the sintering temperature of the low-temperature sintering is 300-400°C, and the sintering time is 8-15 hours; the post-processing includes at least one of crushing, grinding, pulverizing, screening, and demagnetization.
[0026] In a third aspect, the present invention provides a positive electrode plate, which includes the sodium iron sulfate positive electrode material described in the first aspect or the sodium iron sulfate positive electrode material prepared by the preparation method described in the second aspect.
[0027] In a fourth aspect, the present invention provides a sodium ion battery, comprising the positive electrode sheet described in the third aspect.
[0028] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:
[0029] (1) The present invention improves the rate performance and cycle stability of the sodium ferric sulfate positive electrode material by doping the P element into the sodium ferric sulfate matrix and the N element into the carbon coating layer.
[0030] (2) The present invention provides a sodium ion battery polyanion positive electrode material with low cost and excellent rate performance and cycle performance. The surface of the sodium ferric sulfate positive electrode material precursor is modified by amphiphilic molecules including a P-containing hydrophilic end and a N-containing hydrophilic end to form an N / P-doped carbon-coated sodium ferric sulfate positive electrode material. The sodium ferric sulfate positive electrode material is modified by anion doping with P, and the carbon coating layer is doped with N. The amphiphilic molecules are carbonized at low temperature to form a stable carbon film, which can not only improve the air stability of sodium ferric sulfate, but also construct a better ion / electron transfer channel, which makes it easier to stably exert the capacity of the positive electrode material, improve the structural stability of the material, and greatly improve the rate performance and cycle performance of the material. The preparation method is simple and easy, green and environmentally friendly, highly safe, and has broad research prospects and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a schematic diagram of the structure of the solid mixture B prepared in Example 1 of the present invention;
[0033] Figure 2 The XRD diffraction pattern of the sodium iron sulfate positive electrode material prepared in Example 1 of the present invention;
[0034] Figure 3 This is a SEM image of the sodium iron sulfate positive electrode material prepared in Example 1 of the present invention;
[0035] Figure 4 This is a comparison chart of the discharge gram capacity of the sodium iron sulfate positive electrode material prepared in Example 1 of the present invention and Comparative Example 1 at different rates. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0037] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0038] In a first aspect, the present invention provides a sodium ferric sulfate positive electrode material, which includes a sodium ferric sulfate matrix, a surface of which is coated with a carbon coating layer, wherein the sodium ferric sulfate matrix is doped with the element P, and the carbon coating layer is doped with the element N.
[0039] The present invention improves the rate performance and cycle stability of the sodium ferric sulfate positive electrode material by doping the P element into the sodium ferric sulfate matrix and doping the N element onto the carbon coating layer.
[0040] In the above-mentioned sodium iron sulfate positive electrode material, as an optional embodiment, the chemical formula of the sodium iron sulfate matrix is Na 6-2x Fe x (SO4)3, wherein x=1.5~2.0.
[0041] In the above-mentioned sodium iron sulfate positive electrode material, as an optional embodiment, the median particle size Dv50 of the sodium iron sulfate positive electrode material is 2 to 6 μm, for example, 2 μm, 4 μm or 6 μm.
[0042] In the above sodium iron sulfate positive electrode material, as an optional implementation, the thickness of the carbon coating layer is 1 to 10 nm, for example, 1 nm, 3 nm, 5 nm, 7 nm or 10 nm.
[0043] In a second aspect, the present invention provides a method for preparing the sodium iron sulfate positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0044] S1, mixing an iron source, a sodium source and a sulfur source to obtain a sodium iron sulfate precursor A;
[0045] S2, uniformly dispersing the sodium iron sulfate precursor A, the carbon source, and the amphiphilic molecule in an aqueous organic solvent for reaction, and then removing the organic solvent by evaporation to obtain a solid mixture B, wherein the polar hydrophilic end of the amphiphilic molecule includes a P-containing hydrophilic end and an N-containing hydrophilic end, and the non-polar hydrophobic end of the amphiphilic molecule includes a long hydrocarbon chain;
[0046] S3. Sintering the solid mixture B at a low temperature under a protective gas atmosphere, and post-treating the sintered material to obtain the sodium ferric sulfate positive electrode material (doped carbon-coated sodium ferric sulfate positive electrode material).
[0047] In step S2, the present invention adopts a solvent thermal method to prepare, which can avoid serious side reactions of a hydrothermal method.
[0048] The preparation method provided by the present invention adopts aqueous organic solvent to synthesize materials, is green and environmentally friendly, the aqueous organic solvent adopted can be evaporated and recovered, and the preparation method has a simple process flow and low cost.
[0049] The N / P doped carbon coated sodium ferric sulfate positive electrode material provided by the present invention introduces amphiphilic molecules containing N and P during the preparation process, so that the surface of the prepared sodium ferric sulfate precursor A is uniformly coated with a layer of amphiphilic molecules, wherein the polar hydrophilic end of the amphiphilic molecule is composed of a P-containing hydrophilic end and a N-containing hydrophilic end, and the non-polar hydrophobic end is composed of a long hydrocarbon chain, the polar hydrophilic end can be combined with an inorganic material, and the non-polar hydrophobic end can maintain stable steric hindrance between particles. The P-containing hydrophilic end can play a role in anion doping in the process of synthesizing sodium ferric sulfate, the P in the P-containing hydrophilic end can partially replace S, the ion radius of P is larger than that of S, and P doping into the sodium ferric sulfate matrix can expand the lattice, which is beneficial to the migration of sodium ions in the diffusion channel and improves the rate performance of the material. At the same time, P doping can improve the stability of the sodium ferric sulfate material; the N in the N-containing hydrophilic end can form defects in the carbon coating layer on the surface, which is beneficial to the adsorption and storage of sodium ions, further improving the conductivity of the material and improving Na + The migration rate of the same phospholipid molecule is improved by the P-containing hydrophilic end inside the material and the hydrophobic end in the carbon layer. The structural continuity of the carbon layer will strengthen the close combination of sodium iron sulfate and the coated carbon layer, that is, the P-containing hydrophilic end and the N-containing hydrophilic end can promote the close combination of sodium iron sulfate and the carbon layer, ensuring the structural stability of the material. The amphiphilic molecules form a stable carbon film on the surface of the material after low-temperature carbonization, isolating air and moisture, which is beneficial to the conductivity and air stability of the material.
[0050] In the preparation method of the above-mentioned sodium ferric sulfate positive electrode material, as an optional embodiment, the iron source includes at least one of divalent iron compounds, for example, the iron source can be at least one of FeSO4, ferrous nitrate, ferrous oxalate, and ferrous chloride; the sodium source includes at least one of sodium sulfate, sodium carbonate, sodium bicarbonate, sodium fluoride, sodium dihydrogen phosphate, and an organic acid salt of sodium; the sulfur source includes at least one of FeSO4, sodium sulfate, ammonium sulfate, and sodium bisulfate.
[0051] In the above-mentioned method for preparing the sodium ferric sulfate positive electrode material, as an optional implementation, in step S1, the molar ratio of the iron element in the iron source, the sodium element in the sodium source and the sulfur element in the sulfur source is consistent with the molar ratio of the iron element, the sodium element and the sulfur element in the sodium ferric sulfate matrix.
[0052] In the above-mentioned method for preparing the sodium iron sulfate positive electrode material, as an optional implementation, in step S1, the mixing includes ball milling mixing, the ball-to-material ratio of the ball milling mixing is (15-20):1, the rotation speed of the ball milling mixing is 200-500r / min (for example, it can be 200r / min, 300r / min, 400r / min or 500r / min), and the ball milling mixing time is 4-6h.
[0053] In the preparation method of the above-mentioned sodium iron sulfate positive electrode material, as an optional implementation, in step S2, the carbon source includes at least one of acetylene black, biomass nanocarbon, glucose, sucrose, caramel, starch, CNTs, carbon quantum dots, and dextrin. Preferably, the carbon source is low-cost acetylene black; the amphiphilic molecules include phosphate amphiphilic molecules containing nitrogen elements, or the amphiphilic molecules include P-containing amphiphilic molecule organic matter and N-containing amphiphilic molecule organic matter, wherein the phosphate amphiphilic molecules containing nitrogen elements include at least one of phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, aminopolyethylene glycol phospholipids, and sphingomyelin, the P-containing amphiphilic molecule organic matter includes at least one of phospholipid compounds that do not contain N, phosphatidic acid, and cardiolipin, and the N-containing amphiphilic molecule organic matter includes at least one of polyoxyethylene castor oil and polyacrylamide.
[0054] Specifically, the structural formula of the phosphatidylcholine (DLPC) is as follows:
[0055]
[0056] In the preparation method of the sodium ferric sulfate positive electrode material, as an optional embodiment, in step S2, the mass ratio of the sodium ferric sulfate precursor A, the carbon source and the amphiphilic molecule is (95-98): (1-2): (1-3). If the molecular weight of the amphiphilic molecule is too much, the coating layer is too thick, but the coating layer has no capacity. Although the coating layer can enhance the electron / ion transmission and improve the material capacity, the excessively thick coating layer will lead to a decrease in its own capacity. If the molecular weight of the amphiphilic molecule is too little, it will not play the role of coating and doping.
[0057] In the above-mentioned method for preparing sodium iron sulfate positive electrode material, as an optional implementation, in step S2, the dispersion rotation speed is 3000-5000r / min (for example, it can be 3000r / min, 3500r / min, 4000r / min, 4500r / min or 5000r / min), and the dispersion time is 2-4h.
[0058] In the above-mentioned method for preparing the sodium iron sulfate positive electrode material, as an optional implementation, in step S2, the aqueous organic solvent can be recycled and includes at least one of ethanol, propanol, tetrahydrofuran, dipropylene glycol butyl ether, and propylene glycol methyl ether.
[0059] In the above-mentioned method for preparing the sodium iron sulfate positive electrode material, as an optional implementation, in step S2, the reaction temperature is 60-80°C (for example, 60°C, 65°C, 70°C, 75°C or 80°C), and the reaction time is 5-6h.
[0060] In the above-mentioned method for preparing sodium iron sulfate positive electrode material, as an optional embodiment, in step S3, the protective gas includes at least one of nitrogen, argon, hydrogen, and ammonia, preferably argon and hydrogen; the sintering temperature of the low-temperature sintering is 300-400°C (for example, it can be 300°C, 320°C, 340°C, 360°C, 380°C or 400°C), and the sintering time is 8-15h (for example, it can be 8h, 10h, 12h or 15h); the post-treatment includes at least one of crushing, grinding, pulverizing, screening, and demagnetization.
[0061] In a third aspect, the present invention provides a positive electrode plate, the positive electrode plate comprising the sodium iron sulfate positive electrode material described in the first aspect or the sodium iron sulfate positive electrode material prepared by the preparation method described in the second aspect, thereby improving the rate performance and cycle stability of the battery.
[0062] In a fourth aspect, the present invention provides a sodium ion battery, comprising the positive electrode plate described in the third aspect, thereby having high rate performance and cycle stability.
[0063] In the above sodium ion battery, as an optional implementation, the sodium ion battery also includes a negative electrode plate, a separator and an electrolyte.
[0064] In the above-mentioned sodium ion battery, as an optional embodiment, the negative electrode active material on the negative electrode plate includes at least one of graphene, graphene oxide, soft carbon, hard carbon, expanded graphite, silicon, and mesophase carbon microbeads, preferably hard carbon.
[0065] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0066] Example 1
[0067] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, comprising the following steps:
[0068] S1. Ferrous sulfate (FeSO4, iron source and sulfur source) and sodium sulfate (Na2SO4, sodium source and sulfur source) are ball-milled to obtain sodium ferric sulfate precursor Na 2.26 Fe 1.87 (SO4)3 (sodium ferric sulfate precursor A), wherein the molar ratio of iron in ferrous sulfate to sodium in sodium sulfate is 1.87:2.26, the ball-to-material ratio of ball milling is 15:1, the rotation speed of the ball milling is 300 r / min, and the ball milling time is 5 h;
[0069] S2, sodium iron sulfate precursor A, acetylene black, and phosphatidylcholine are added to a closed reactor at a mass ratio of 96:2:2, and are evenly dispersed in anhydrous n-propanol at a solid-liquid ratio of 1:1.5, heated to 70°C, reacted for 5 hours, and after the reaction is completed, the anhydrous n-propanol is evaporated to obtain a solid mixture B. The structural schematic diagram of the solid mixture B is shown in Figure 1 As shown, the dispersion speed is 4000r / min and the dispersion time is 3h;
[0070] S3. Sinter the solid mixture B at 380°C for 12 hours in a 97% Ar + 3% H2 atmosphere (the volume ratio of Ar:H2 is 97:3), and crush the sintered material to obtain an N / P-doped carbon-coated sodium ferric sulfate positive electrode material (sodium ferric sulfate positive electrode material). The median particle size Dv50 of the positive electrode material is 3 μm, and the thickness of the carbon coating layer is 3-5 nm.
[0071] Figure 2 is the XRD diffraction pattern of the sodium iron sulfate positive electrode material prepared in this example, Figure 2 It can be seen that the characteristic peaks of the synthesized sodium iron sulfate positive electrode material correspond well.
[0072] Figure 3This is the SEM image of the sodium iron sulfate positive electrode material prepared in this example. Figure 3 It can be seen that the synthesized sodium iron sulfate positive electrode material is a spherical structure with a particle size of about 3um.
[0073] Example 2
[0074] The preparation method of the sodium iron sulfate positive electrode material provided in this embodiment is basically the same as that in Example 1, except that in step S2, the mass ratio of the sodium iron sulfate precursor A to acetylene black and phosphatidylcholine is 97:2:1.
[0075] Example 3
[0076] The preparation method of the sodium iron sulfate positive electrode material provided in this embodiment is basically the same as that in Example 1, except that in step S2, the mass ratio of the sodium iron sulfate precursor A to acetylene black and phosphatidylcholine is 95:2:3.
[0077] Example 4
[0078] The preparation method of the sodium iron sulfate positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that, in step S2, phosphatidylcholine is replaced by phosphatidylserine.
[0079] Example 5
[0080] The preparation method of the sodium iron sulfate positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step S3, the 97% Ar+3% H2 atmosphere is replaced by a 100% Ar atmosphere.
[0081] Example 6
[0082] The preparation method of the sodium iron sulfate positive electrode material provided in this embodiment is basically the same as that in Example 1, except that in step S1, the ball-to-material ratio of the ball milling mixture is 18:1, the rotation speed of the ball milling mixture is 500 r / min, and the ball milling mixing time is 4 h; in step S2, the dispersion rotation speed is 5000 r / min, and the dispersion time is 2 h.
[0083] Comparative Example 1
[0084] This comparative example provides a method for preparing a sodium iron sulfate positive electrode material, comprising the following steps:
[0085] S1. Ferrous sulfate (FeSO4, iron source and sulfur source) and sodium sulfate (Na2SO4, sodium source and sulfur source) are ball-milled to obtain sodium ferric sulfate precursor Na 2.26 Fe 1.87(SO4)3 (sodium ferric sulfate precursor A), wherein the molar ratio of iron in ferrous sulfate to sodium in sodium sulfate is 1.87:2.26, the ball-to-material ratio of ball milling is 15:1, the rotation speed of the ball milling is 300 r / min, and the ball milling time is 5 h;
[0086] S2, adding sodium iron sulfate precursor A and acetylene black in a mass ratio of 96:4 to a closed reactor, and uniformly dispersing them in anhydrous n-propanol at a solid-liquid ratio of 1:1.5, heating to 70°C, reacting for 5 hours, and evaporating the anhydrous n-propanol after the reaction is completed to obtain a solid mixture B, wherein the dispersion speed is 4000r / min, and the dispersion time is 3h;
[0087] S3. The solid mixture B is sintered at 380° C. for 12 h in a 97% Ar+3% H2 atmosphere (the volume ratio of Ar:H2 is 97:3). The sintered material is crushed to obtain a carbon-coated sodium iron sulfate positive electrode material.
[0088] Comparative Example 2
[0089] The preparation method of the sodium iron sulfate positive electrode material provided in this comparative example is basically the same as that in Example 1, except that in step S2, phosphatidylcholine is replaced by polyoxyethylene castor oil.
[0090] The structure of polyoxyethylene castor oil in this comparative example is shown below:
[0091]
[0092] Comparative Example 3
[0093] The preparation method of the sodium iron sulfate positive electrode material provided in this comparative example is basically the same as that in Example 1, except that in step S2, anhydrous n-propanol is replaced by deionized water.
[0094] Performance Testing
[0095] Preparation of button battery: In a glove box, the positive electrode sheet prepared from the positive electrode materials of the embodiment and the comparative example, the glass fiber separator and the electrolyte, and the counter electrode (sodium sheet) were assembled in sequence to obtain a CR2032 button battery. The electrolyte used was EC+DEC+EMC (volume ratio of 1:1:1) with 1.15 mol / L NaPF6, and the additive DFP was 2%.
[0096] Preparation of soft-pack batteries: The positive electrode sheets, hard carbon negative electrode sheets and polyethylene diaphragms (PE+OBS diaphragms) prepared from the positive electrode materials of the embodiments and comparative examples are stacked and assembled and baked until the moisture content is qualified, the electrolyte is injected, and the batteries are packaged after hot pressing and high-temperature standing. After volume separation, the batteries are stood at room temperature to obtain soft-pack 505060 finished batteries. The electrolyte used is 1.15 mol / LNaPF6 EC+DEC+EMC (volume ratio 1:1:1), and the additive DFP is 2%.
[0097] Air stability evaluation: After the positive electrode materials of the embodiment and the comparative example were placed in air for 0 month and 1 month, they were assembled into button cells respectively, and the 0.1C discharge capacity of the materials was tested. The charge and discharge voltage window was 2.0V~4.4V. The test results are shown in Table 1.
[0098] Material rate stability: The material rate stability of the charged material was tested at 25°C on an electrochemical workstation battery test system. The current densities tested were 0.1C, 0.5C, 1C, 5C, 10C, 20C, and 0.1C, respectively. The charge and discharge voltage window was 2.0V to 4.4V. The average value of the discharge capacity in grams during 10 charge and discharge cycles at the corresponding current density was taken as the discharge capacity in grams at the current density. The test results are shown in Tables 1 and Figure 4 .
[0099] Material cycle stability: The material cycle stability of the soft pack was tested at 25°C on an electrochemical workstation battery test system. The charge and discharge current density was 1C / 1C, and the charge and discharge voltage window was 2.0V to 4.3V. The test results are shown in Table 1.
[0100] Table 1
[0101]
[0102]
[0103] From Table 1 we can at least see that:
[0104] (1) By comparing Example 1 with Comparative Example 1, it can be seen that the present invention improves the rate performance and cycle stability of the sodium ferric sulfate positive electrode material by doping the sodium ferric sulfate matrix with P elements and doping the carbon coating layer with N elements. The N / P doped carbon-coated sodium ferric sulfate positive electrode material, on the one hand, has a stable carbon film formed on the material surface by low-temperature carbonization of its phospholipid-based amphiphilic molecules, which improves the air stability of the sodium ferric sulfate, so that the gram capacity of the positive electrode material does not decay after being placed in the air for 1 month. On the other hand, the sodium ferric sulfate positive electrode material can be modified by anion doping with P, and defects are formed in the carbon coating layer by N, so as to construct a better ion / electron transfer channel, so that the material still has a high gram capacity at a high rate of 20C. At the same time, the P-containing hydrophilic end and the N-containing hydrophilic end can promote the close combination of the sodium ferric sulfate and the carbon layer, ensure the structural stability of the material, and optimize the material cycle performance.
[0105] (2) By comparing Example 1 with Comparative Example 2, it can be seen that only the N-doped carbon coating layer is introduced, and the sodium iron sulfate positive electrode material is not modified by anion doping. The stability and rate performance of the material are reduced, which is manifested in low gram capacity at a high rate of 20C and poor 1C / 1C cycle performance.
[0106] (3) By comparing Example 1 with Comparative Example 3, it can be seen that when the solid mixture B is prepared by the hydrothermal method in step S2, the stability and rate performance of the material are reduced, which is manifested as low gram capacity at a high rate of 20C and poor 1C / 1C cycle performance. The reason may be that the hydrothermal method has serious side reactions and a high impurity content, which reduces the electrochemical performance of the prepared positive electrode material.
[0107] (4) By comparing Example 1 with Example 5, it can be seen that when the 97% Ar + 3% H2 atmosphere is replaced by a 100% Ar atmosphere, the air stability, rate performance and cycle performance of the material are all reduced. The reason is that: Fe 2+ It is easy to be oxidized, thus affecting the reactivity of the material. Adding reducing gas H2 can reduce trivalent Fe and ensure Fe 2+ stable existence.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sodium iron sulfate positive electrode material, characterized in that: The sodium ferric sulfate positive electrode material comprises a sodium ferric sulfate matrix, the surface of which is coated with a carbon coating layer, wherein the sodium ferric sulfate matrix is doped with P element, and the carbon coating layer is doped with N element.
2. The sodium iron sulfate positive electrode material according to claim 1, characterized in that The chemical formula of the sodium ferric sulfate matrix is Na 6-2x Fe x (SO4)3, wherein x = 1.5 to 2.0; And / or, the median particle size Dv50 of the sodium iron sulfate positive electrode material is 2 to 6 μm; And / or, the carbon coating layer has a thickness of 1 to 10 nm.
3. A method for preparing the sodium iron sulfate positive electrode material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1, mixing an iron source, a sodium source and a sulfur source to obtain a sodium iron sulfate precursor A; S2, uniformly dispersing the sodium iron sulfate precursor A, the carbon source, and the amphiphilic molecule in an aqueous organic solvent for reaction, and then removing the organic solvent by evaporation to obtain a solid mixture B, wherein the polar hydrophilic end of the amphiphilic molecule includes a P-containing hydrophilic end and an N-containing hydrophilic end, and the non-polar hydrophobic end of the amphiphilic molecule includes a long hydrocarbon chain; S3, sintering the solid mixture B at a low temperature under a protective gas atmosphere, and post-treating the sintered material to obtain the sodium iron sulfate positive electrode material.
4. The method for preparing the sodium iron sulfate positive electrode material according to claim 3, characterized in that: The iron source includes at least one of FeSO4, ferrous nitrate, ferrous oxalate, and ferrous chloride; the sodium source includes at least one of sodium sulfate, sodium carbonate, sodium bicarbonate, sodium fluoride, sodium dihydrogen phosphate, and an organic acid salt of sodium; the sulfur source includes at least one of FeSO4, sodium sulfate, ammonium sulfate, and sodium bisulfate; And / or, in step S1, the molar ratio of the iron element in the iron source, the sodium element in the sodium source and the sulfur element in the sulfur source is consistent with the molar ratio of the iron element, the sodium element and the sulfur element in the sodium ferric sulfate matrix; And / or, in step S1, the mixing includes ball milling mixing, the ball-to-material ratio of the ball milling mixing is (15-20):1, the rotation speed of the ball milling mixing is 200-500 r / min, and the ball milling mixing time is 4-6 h.
5. The method for preparing the sodium iron sulfate positive electrode material according to claim 3, characterized in that: In step S2, the carbon source includes at least one of acetylene black, biomass nanocarbon, glucose, sucrose, caramel, starch, CNTs, carbon quantum dots, and dextrin; the amphiphilic molecules include phosphate amphiphilic molecules containing nitrogen elements, or the amphiphilic molecules include P-containing amphiphilic molecule organic matter and N-containing amphiphilic molecule organic matter, wherein the phosphate amphiphilic molecules containing nitrogen elements include at least one of phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, aminopolyethylene glycol phospholipids, and sphingomyelin, the P-containing amphiphilic molecule organic matter includes at least one of phospholipid compounds that do not contain N, phosphatidic acid, and cardiolipin, and the N-containing amphiphilic molecule organic matter includes at least one of polyoxyethylene castor oil and polyacrylamide.
6. The method for preparing the sodium iron sulfate positive electrode material according to claim 3, characterized in that: In step S2, the mass ratio of the sodium iron sulfate precursor A, the carbon source and the amphiphilic molecule is (95-98):(1-2):(1-3).
7. The method for preparing the sodium iron sulfate positive electrode material according to claim 3, characterized in that: In step S2, the dispersion speed is 3000-5000 r / min, and the dispersion time is 2-4 h; And / or, in step S2, the reaction temperature is 60-80°C, and the reaction time is 5-6h; And / or, in step S2, the aqueous organic solvent includes at least one of ethanol, propanol, tetrahydrofuran, dipropylene glycol butyl ether, and propylene glycol methyl ether.
8. The method for preparing the sodium iron sulfate positive electrode material according to claim 3, characterized in that: In step S3, the protective gas includes at least one of nitrogen, argon, hydrogen, and ammonia; the sintering temperature of the low-temperature sintering is 300-400°C, and the sintering time is 8-15 hours; the post-processing includes at least one of crushing, grinding, pulverizing, screening, and demagnetization.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the sodium iron sulfate positive electrode material according to claim 1 or 2 or the sodium iron sulfate positive electrode material prepared by the preparation method according to any one of claims 3-8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Controllable synthesis method for nitrogen and phosphorus co-doped graphitized carbon ball with hollow structure
CN103183330A
Sodium ion battery
CN116404144A
Preparation method of two-phase modified sodium ferric sulfate positive electrode material
CN117691087A
Preparation method of simple carbon-coated anion-doped sodium ferric sulfate as sodium ion battery positive electrode material
CN118164458A
Processing method of flow battery electrode material, flow battery electrode material and flow battery
CN118472283A
Cited By
Composite carbon-coated sodium ferrous sulfate positive electrode material as well as preparation method and application thereof
CN120413642A
